End of Ban on Women Driving in Saudi Arabia- Implications for Automobile Brands - Ahmad, Farah; Mahfooz, Yasser (Archives of Business Research, 2019)
The objective of this study is to determine the role of brand equity in generating trust and purchase intention towards passenger cars in the Kingdom of Saudi Arabia. Data was collected from females in Riyadh, Jeddah and Dammam, which are among the largest cities in the country. The study used an online questionnaire with a convenience sampling technique. Out of 231 responses, 226 were found valid. The data was analyzed for descriptive statistics and also the significant relationship among various constructs. The respondents reported high levels of brand equity and significant relationship was found between all constructs in the conceptual model. Out of all the dimensions of brand equity, perceived quality had the maximum effect on brand equity. The car manufacturers need to recognize the importance of brand equity dimensions, and implement appropriate strategy to increase the brand trust and purchase intention of female customers.